Digital preservation for libraries, archives, and museums - Corrado, Edward M.; Moulaison Sandy, Heather (Rowman & Littlefield, 2017)
This new edition of Digital Preservation for Libraries, Archives, and Museums is the most current, complete guide to digital preservation available today. For administrators and practitioners alike, the information is presented in a readable fashion, focusing on management issues and best practices.